The export-led growth hypothesis revisited: theory and evidence - Ahumada, Hildegart; Sanguinetti, Pablo (Estudios de Economía, 2016)
Export growth is often singled out as a key aspect in processes of fast and sustainable increases in per capita income. In this paper we revisit this export-led growth hypothesis (ELGH). From an empirical point of view we study this phenomenon applying Granger-type tests on panel data. The results seem to confirm that, for the sample of countries and the period under study, exports did behave as the “engine of growth” as they Granger-caused investment, output growth and imports. In the theoretical part of the paper we reframe the ELGH standard model in terms of recent models of endogenous growth so as to make it more consistent with these empirical findings.